Comparison of Early Postoperative Outcome Between Intermittent Intravenous Heparin versus Continuous Heparin Infusion after Initial Bolus Dose during Off-Pump Coronary Artery Bypass Surgery - Shimul, Md Shahriar Kabir; Alam, AKM Manzurul; Haque, Al Masum Ziaul; Hoque, Asraful; Hossain, Abdullah Al Mamun; Rahman, Md Mizanur; Islam, Md Amirul; Siddiqi, Nurul Alam; Ahmed, Imran; Al Nur, M Asmaul Alam; Reza, Amina; Ahmed, Masud; et al. (Cardiovascular Journal, 2023)
Background: Heparin is an anticoagulant used invariably in all cardiac surgery. Heparin dosing and its reversal is determined by monitoring Activated Clotting Time (ACT). Surgery under cardiopulmonary bypass requires much more heparin than off-pump cardiac operations. Intermittent heparin dosing after initial bolus dose is widely practiced to maintain ACT level 200- 300 seconds in OPCAB. Fluctuation of ACT level from this range may causes adverse postoperative outcome. This study was aimed to compare early postoperative outcome between intermittent heparin dose and continuous heparin infusion after initial bolus dose during OPCAB. Methods: This comparative cross-sectional study was carried out in National Institute of Cardiovascular Diseases (NICVD) from January 2019 to December 2020. Total 110 patients were enrolled by purposive sampling and divided into 2 groups: group-A where 55 patients received intermittent heparin after initial bolus dose and group-B where 55 patients received continuous heparin infusion after initial bolus dose. Data were analyzed by statistical package for social science (SPSS) version 26.0 and p value <0.05 was considered significant. Results: Baseline ACT level of group-A was 87.04±5.51 seconds and group-B was 87.31±5.74 seconds, which was not significant (p = 0.800). After bolus dose of Heparin, ACT level of group-A was 252.02 ± 25.131 seconds and group-B was 259.04 ± 12.645 seconds. Difference between the groups was not significant (p = 0.068). Mean maintenance ACT was 326.34±22.774 seconds in group-A and 258.67±12.285 seconds in group-B patient, which was significant (p<0.001). Peroperatively 29% from group-A and 11% from group-B developed arrhythmia. Postoperative mean Troponin I level in group-A was 5.78± 1.15 and group-B was 5.32± 1.05 ng/dl, which is significant (p = 0.030). Postoperative blood loss was significantly higher in group-A than group-B (986.36± 398.31 vs 852.73±241.22, p=0.036). There was significantly better reduction of arrhythmia and ischemia in postoperative and on discharge ECG finding in group-B patients (p=0.002). On discharge echocardiography 31% from group-A and 13% from group-B had regional wall motion abnormality, which is significant (p=0.018). But there was no significant difference in LVEF% (52.65±5.99 vs 53.85±5.77, p = 0.287). There was only one mortality which was from group-A. The patient was suffering from critical left main disease and developed postoperative arrhythmia and low output syndrome. Conclusion: Early postoperative outcome of continuous heparin infusion is better than intermittent intravenous heparin after initial bolus dose during Off-pump coronary artery bypass surgery. So, during OPCAB use of continuous heparin infusion after bolus dose is eminent time worthy. Cardiovasc j 2023; 16(1): 17-23